IMPROVEMENT OF METHODS FOR ACCOUNTING AND ANALYSIS OF FINANCIAL RESULTS OF ORGANIZATIONS IN THE CONTEXT OF DIGITAL TRANSFORMATION OF THE ECONOMY - Igamberdieva Kunduz Ergashevna (Modern American Journals, 2025)
The digital transformation of the economy has fundamentally altered the conditions under which organizations form, record, and analyze their financial results. The rapid development of digital technologies, including enterprise resource planning systems, cloud accounting platforms, big data analytics, and artificial intelligence, has expanded the possibilities of financial information processing while simultaneously increasing methodological and analytical challenges. This study examines the improvement of accounting and analytical methods for financial results in the context of digital transformation, with particular emphasis on ensuring the relevance, reliability, and analytical value of financial information for managerial and external decision-making. The research focuses on the evolution of traditional accounting approaches toward integrated digital models that enable real-time data processing, enhanced transparency, and deeper analytical insights into organizational performance. Special attention is given to the transformation of accounting functions from predominantly retrospective recording to proactive analytical support of strategic management. The study highlights the role of digital tools in improving the accuracy of income and expense recognition, optimizing cost allocation, and strengthening analytical procedures used to assess profitability, efficiency, and financial sustainability. The findings demonstrate that the systematic integration of digital technologies into accounting and analysis contributes to higher quality financial results assessment and supports more informed economic decisions in modern organizations.
Keywords: Financial results, accounting methodology, financial analysis, digital transformation, digital accounting systems, management decision-making, economic efficiency, data analytics.